Superb Microvascular Imaging of Palatine Tonsils in Healthy Children: A Preliminary Study. Issue 2 (June 2018) - Caliskan, Emine; Ozturk, Mehmet; Bayramoglu, Zuhal; Adaletli, Ibrahim
Abstract : Abstract: In healthy children, the normal vascularity index (VI) values were defined for palatine tonsils using the superb microvascular imaging (SMI), and the relationship with potential factors affecting these values was assessed. This prospective study evaluated 74 children (age range = 3–17 years, median = 13 years, SD = 6.4 years). The cases were divided into 3 subgroups based on age as 3 to 6 years (preschool), 7 to 12 years (school age), and 13 to 17 years (adolescent). Demographic data such as sex, age, and body mass index (BMI) were recorded. The VI values of tonsils were measured with SMI and power Doppler (PD), and the correlation with descriptive data was researched. The Student t test, Mann-Whitney U test, and Spearman ρ correlation coefficient were used. The mean VI values on the right tonsil were calculated as 7.5% and 2.6% and on the left tonsil were 6.5% and 2.3% according to SMI and PD, respectively. On SMI, the vascularity was similar in the preschool and school-age groups, with a significant reduction between the school-age and adolescent groups. As BMI increased, tonsil vascularity reduced on SMI and PD. There was no significant difference in tonsil vascularity between the sexes. The VI values were identified to be higher on SMI compared with PD ( P = 0.001). In healthy children, the normal VI values for both tonsils were determined with SMI and PD. On SMI, tonsil vascularity reduced significantly in the transition from school age to adolescence. Tonsil vascularity was affected by variations in BMI.